(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The pathogenesis in the development of caries and non-carious lesions, inflammatory periodontal diseases and diseases of the oral mucosa is described. The manifestations of these diseases are most often due to a pronounced sensitization of the body to harmful production factors, in the oral cavity there is a pronounced change in local immunity, homeostasis with the manifestation of dysbiosis, as a result of which the features of their clinical manifestations change.